Swartkrans Paranthropus and Sterkfontein Australopithecus from southern Africa had different locomotor repertoires - Marine Cazenave; Annalisa Pietrobelli; Andrea Luková; Sebastian Bachmann; Matthew V. Caruana; Ronald J. Clarke; Christopher J. Dunmore; Ashley S. Hammond; Jason L. Heaton; A. J. Heile; Jakobus Hoffman; Kathleen Kuman; et al. (Proceedings of the National Academy of Sciences, 2026)
Southern African hominin fossils traditionally attributed to Paranthropus robustus and Australopithecus africanus are differentiated from each other by their dentition and cranial architecture, but their postcranial anatomy has typically been regarded functionally as broadly similar (i.e., terrestrial bipedalism with some degree of arboreal locomotion). Testing the hypothesis of a similar locomotor repertoire between these two taxa has been complicated by a lack of postcranial fossils attributable to P. robustus . Here, we detail our comparative examination of the internal bone anatomy of a recently described c. 1.8 Ma P. robustus articulating femur and tibia, which suggests distinct patterns of joint loading and locomotor behavior. Our analysis of cortical bone in the hip and trabecular bone in the ankle, knee, and hip joints suggests that P . robustus habitually adopted a high frequency of ankle, knee, and hip flexion, as required for climbing, while Australopithecus from a c. 3.4 Ma level at the site of Sterkfontein displays a more modern human-like structural pattern across the lower limb joints consistent with comparatively more frequent terrestrial bipedalism. These results reveal that geologically younger P . robustus likely used arboreality more frequently than older Sterkfontein Australopithecus . Together with differences in masticatory behavior, this line of evidence indicates that these two hominin taxa occupied distinct ecological niches.